RELATIONSHIP BETWEEN CAPITAL STRUCTUR FACTORS AND FIRM PERFORMANCE - Yusfiarto, Rizaldi (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2020)
Measurement of firm performance becomes very important for management to evaluate and planning for future goals. Several factors can affect firm performance, including profitability, ownership structure, and company size. For that this study aims to examine the effect of profitability, ownership structure, company size on firm performance with capital structure as an intervening variable. Data obtained during the period 2016-2018 from manufacturing companies listed on the Indonesia Stock Exchange. The results in this study indicate profitability, ownership structure and firm size simultaneously (together) affect the capital structure. Profitability, ownership structure, firm size, and capital structure simultaneously (together) affect the firm's performance.